Lattice dynamics and phase transition of acetylene - Gamba de Hernando, Zulema; Bonadeo, H. A. (American Institute of Physics, 1982)
Fil: Gamba de Hernando, Zulema Comisión Nacional de Energía Atómica; Argentina